Age dynamics of the level of development of static equilibrium in middle-class students with visual impairments - Liliana Riadova; Liudmyla Shesterova (Kharkiv State Academy of Physical Culture, 2018)
Purpose: to study the age-related dynamics of indicators of the ability to maintain static equilibrium in middle-class students with visual impairments. Material & Methods: static equilibrium indices were determined by the method of E. Ya. Bondarevsky. The study was attended by middle school students with impaired view of the communal institution "Kharkiv Special Boarding School I-III Steps 12" Kharkiv Regional Council. Results: peculiarities of the dynamics of static equilibrium in children of secondary school age with visual impairment, depending on age and sex. Conclusions: it was revealed that the indices of static equilibrium on one leg, both with the eyes open and with the eyes closed, vary with age in different directions with age. The girls observed mostly the best indicators of static balance with their eyes open, the boys - with closed.